The features of expression of constitutive isoforms of the nitric oxide synthase in paraventricular and supraoptic nuclei of the hypothalamus in hypertension of different origins - Yu. M. Kolesnyk; O. V. Hancheva; N. V. Kuzo (Zaporozhye State Medical University, 2015)
Aim. The purpose was to evaluate the features of the neuronal and endothelial nitric oxide synthase expression pattern in supraoptic and magnocellular part of paraventricular nuclei of the hypothalamus in different models of hypertension. Materials and methods. The study was carried out on 20 Wistar male rats and 10 SHR male rats. There were two experimental models of hypertension used: the genetically predisposed to age-related hypertension SHR and rats with endocrine-saline model of hypertension (ESM). The object was the hypothalamus of rats. The immunohystochemical assay was used to determine the expression of NOS isoforms. Results showed the imbalance of constitutive NOS isoforms in SON and PVN of hypothalamus in both of SHR and ESM. The eNOS and nNOS expression pattern is dependent on etiological factor, topographical peculiarities of the nuclei and their functions. Conclusions. We believe the imbalance of constitutive NOS isoforms take part in the hypertension development, its progression and the formation of complications.